2013
DOI: 10.1105/tpc.112.107219
|View full text |Cite
|
Sign up to set email alerts
|

The WD40-Repeat Proteins NFC101 and NFC102 Regulate Different Aspects of Maize Development through Chromatin Modification

Abstract: The maize (Zea mays) nucleosome remodeling factor complex component101 (nfc101) and nfc102 are putative paralogs encoding WD-repeat proteins with homology to plant and mammalian components of various chromatin modifying complexes. In this study, we generated transgenic lines with simultaneous nfc101 and nfc102 downregulation and analyzed phenotypic alterations, along with effects on RNA levels, the binding of NFC101/NFC102, and Rpd3-type histone deacetylases (HDACs), and histone modifications at selected targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 55 publications
(98 reference statements)
1
16
0
Order By: Relevance
“…We cloned and sequenced cDNAs derived from the ZCN7 and ZCN8 antisense RNAs of B73 and teosinte plants and found that they encode very short putative open reading frames with no homology to known proteins (Supplemental Fig. S4; Mascheretti et al, 2013). Therefore, these antisense transcripts may represent long noncoding RNAs (lncRNAs).…”
Section: Analysis Of Specific Zcn7 and Zcn8 Transcriptsmentioning
confidence: 99%
See 4 more Smart Citations
“…We cloned and sequenced cDNAs derived from the ZCN7 and ZCN8 antisense RNAs of B73 and teosinte plants and found that they encode very short putative open reading frames with no homology to known proteins (Supplemental Fig. S4; Mascheretti et al, 2013). Therefore, these antisense transcripts may represent long noncoding RNAs (lncRNAs).…”
Section: Analysis Of Specific Zcn7 and Zcn8 Transcriptsmentioning
confidence: 99%
“…A recent report used a combination of RNA blotting with strand-specific probes and RT-PCR with locusand strand-specific primers to show that ZCN8 produces three transcript isoforms (Mascheretti et al, 2013). These isoforms correspond to (1) the processed sense mRNA, which accumulates only in mature leaf; (2) a very low amount of unspliced sense-strand premRNA present both in meristematic enriched regions and in mature leaf; and (3) an unspliced antisense RNA strand, which represents the prevalent form of unspliced transcript and is produced not only in leaves but also in various other tissues (Fig.…”
Section: Analysis Of Specific Zcn7 and Zcn8 Transcriptsmentioning
confidence: 99%
See 3 more Smart Citations